Rancang Bangun Sistem Informasi Simpan Pinjam Studi Kasus: KSP Berkah Dana Mandiraja - Yustina Meisella Kristania; Ina Maryani; Afit Muhammad Lukman; Eris Br Sipayung (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2018)
Seeing the speed of the development of information technology world very quickly by utilizing the tasks in various fields, the cooperative as a business entity with the role of improving people's living standards must also experience technological progress, but there are still some weaknesses in the procedure of savings and loans in KSP Blessing Fund Mandiraja, is false data entry, report generation, unorganized data, stacking and archival destruction. The purpose of this research is to make information system. The design of this software using DFD, ERD, data dictionary and LRS. Data using the method of clarity and workmanship KSP. The author also conducted a review of literature related to the problem. In the software development model using the waterfall model. Hopefully with the existence of saving and loan information system, the related process becomes easier. This system can display and manage data information and submission of savings and lending.